Mathematical model simulating the ignition of a droplet of coal water slurry containing petrochemicals; Energy; Vol. 150 - Glushkov D. O. Dmitry Olegovich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Syrodoy S. V. Semen Vladimirovich (2018, 2018)
Title screen